Characteristics of Advanced Epithelial Ovarian Cancer Patients in Dr. M. Jamil Padang Hospital - Azwan, Reyhan Julio; Muhammad, Syammel; Karmia, Hudila Rifa (Fakultas Kedokteran Universitas Andalas, 2024)
Background: Ovarian cancer is a major global health concern, often diagnosed at advanced stages, impacting five-year survival rates. This study examines the demographic and clinical characteristics of 64 patients with advanced epithelial ovarian cancer, shedding light on the disease complexity. Methods: Conducted at General Hospital Dr. M. Djamil Padang, this cross-sectional study analyzed patient data using SPSS. The research, approved by the Health Research Ethics Committee of Andalas University, included detailed demographic and clinical assessments. Results: Predominantly, patients were aged 40-64, exhibited normal BMI, and a significant portion had not given birth. Evaluation of clinical factors, including Peritoneal Cancer Index (PCI) and residual tumor size, provided insights into the cohort's characteristics. Optimal cytoreduction (<1 cm residual tumor) was prevalent, emphasizing the role of surgery in enhancing survival. Conclusion:The study underscores the multifaceted nature of advanced epithelial ovarian cancer and advocates personalized treatment approaches tailored to individual patient profiles. The findings contribute valuable insights to the existing knowledge, emphasizing the importance of age, BMI, and surgical interventions in influencing outcomes.